Glutathione-S-transferase production in earthworm (Annelida: Eudrilidae) as a tool for heavy metal pollution assessment in abattoir soil - Folarin, Owagboriaye (2016)
The use of direct response of animals to environmental challenges by production of biomarkers is a better tool to assess environmental pollution than the conventional methods. This study aimed to measure Glutathione-S-transferase (GST) in earthworms as tools for assessing heavy metal pollution in abattoir soil. Five (5) replicates each of earthworm species (Libyodrilus violaceous, Eudrilus eugeniae and Alma millsoni), soil and rumen waste samples were collected from three (3) abattoir sites (Lafenwa, Gbonogun and Madojutimi abattoirs), and a control site located within Federal University of Agriculture Abeokuta, beside an undisturbed stream with no rumen waste. Heavy metal (Cu, Zn, Pb, Cd, Co, Cr, Ni and Mn) concentrations in rumen waste, abattoir soils and earthworm tissues were determined using Atomic Absorption Spectrophotometer. The pH and organic matter (OM) concentrations of the rumen waste and abattoir soils were determined by standard methods. GST activities in the earthworm tissues were determined through the conjugation of 1 mM reduced glutathione (GSH) with 1 mM 1-chloro-2,4-dinitrobenzene (CDNB). The rumen waste recorded significantly higher (p ≤ 0.05) % OM, heavy metal concentrations and pH level than in their respective abattoir soils. The mean heavy metal concentrations of Cu, Zn, Pb, Cd and Mn were highest in the tissue of earthworm species obtained from Lafenwa abattoir. A significantly (p ≤ 0.05) higher GST activities were recorded in the tissue of earthworm species obtained from Lafenwa and Gbonogun abattoirs. Libyodrilous violaceus obtained from Lafenwa abattoir recorded the highest GST activity (8.47±1.39) in their tissue followed by the ones from Gbonogun abattoir (8.21±0.85). A significant (p ≤ 0.05) positive correlations was observed between GST activities in earthworm tissues and heavy metal concentrations. GST activities can therefore be used to assess the level of heavy metal pollution in abattoir soils.